CAPSICUM COMPOSITION MITIGATES OBESITY: EFFECTS ON METABOLIC PROFILES AND KEY TISSUE BIOMARKERS IN HIGH-FAT DIET-FED RATS - Şahin, Nurhan; Kekec, Erdal; Kayri, Veysi; Orhan, Cemal; Ozmen, Busra; Ozercan, Ibrahim; Şahin, Kazım (Poznan Univ Life Sciences, 2026)
Background. The metabolic effects of capsicum in organisms fed a high-fat diet (HFD) remain unclear. This study investigated the impact of a capsicum composition on metabolic parameters and key molecular markers - including PPAR-gamma, IRS-1, glucose transporters, and NF-kappa B - to assess its anti-obesity effects. Materials and methods. Rats were divided into four groups: (1) control; (2) capsicum compositions (CC), rats fed a standard diet with oral administration of capsicum compositions; (3) high-fat diet (HFD), rats fed a high-fat diet; and (4) HFD+CC, rats fed an HFD with oral administration of capsicum compositions. Results. CC supplementation significantly reduced final body weight, visceral fat mass, and liver weight in the HFD-fed rats (p < 0.001). The HFD+CC group also showed significant decreases in serum glucose, insulin, total cholesterol, triglycerides, and free fatty acids (p < 0.05). In addition, CC administration to rats on a high-fat diet reduced malondialdehyde (MDA) concentrations and increased serum total antioxidant capacity (TAC) (p < 0.05). Moreover, CC significantly increased liver GLUT-2, PPAR-gamma, and IRS-1 levels (p < 0.001). Conclusion. The capsicum composition effectively attenuated HFD-induced metabolic disturbances by modulating glucose and lipid homeostasis and improving oxidative status.
Keywords: capsicum; high-fat diet; oxidative stress; metabolic profile